CHOICE, SUPPORT AND INCLUSION: IMPLEMENTING ARTICLE 19 OF THE CONVENTION ON THE RIGHTS OF PERSONS WITH DISABILITIES IN KENYA (African Disability Rights Yearbook, 2021)
This article examines article 19 of the United Nations Convention on the Rights of Persons with Disabilities (CRPD), which comprises the right to live independently and to be included in the community, from an African perspective. The context is one in which persons with disabilities live with their families but without individualised state funded support services, against a cultural backdrop consisting of a largely communal way of life. This article examines the import of article 19, tracing its history and looking at various sources to flesh out the nature and content of the right to live independently in the community. It then gives content to the core of article 19 in the Kenyan setting, providing guidance on what the essential components of a policy that promotes article 19 in Kenya should be. This article makes policy proposals which are geared towards ensuring choice, support and inclusion of PWDs in Kenya.
Keywords: United Nations Convention; Rights of Persons with Disabilities; Kenya; right to live independently; communal way of life